THE STUDY OF BEHAVIOR EVALUATION SURVEY: FAMILY HEALTH - Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitriani Fitriani; Fitrah Reynaldi (Universitas Teuku Umar, 2018)
The Family health is one of the efforts in health development to encourage overall human development which needs to be considered early on. Ministry of Health 2013, households in Indonesia with PHBS reached 55.6%. Bale Village has health problems that are not paying attention to the cleanliness of the surrounding environment, such as littering, food waste that causes flies and can cause various diseases such as diarrhea. This survey research was conducted in July 2018 which aims to see how behavioral evaluations will affect family health. The research population of all communities in PT. Mifa Brothers in West Aceh Regency as many as 261 houses with a sample using total sampling, which is 261 houses with the target interview (Indep Interview) is the head of the family and mother. Data were analyzed univariately and by measurement of a healthy family index. The results of the study found that the low healthy living behavior of the community by not using family planning was 143 households (54.8%), while for smokers' families were 245 households (93.9%). It can be concluded that the number of unhealthy families is 178 households (68.2%), the number of healthy families is 83 households (31.8%), the total number of healthy families index is 31.8% of all unhealthy families. It is expected that the community will be able to increase knowledge of healthy behaviors that will affect family health by coordinating with relevant agencies in various health programs.